Proximal Fibular Osteotomy Vs Proximal Fibular Osteotomy with Intra-Articular Hyaluronic Acid: Difference in Terms of Pain Relief and Functional Outcome - Naseem Munshi; Muhammad Khalid; Muhammad Naseem; Khadijah Abid (ziauddin University, 2024)
Background: Knee osteoarthritis (OA) is a complex, progressive illness marked by cartilage deterioration and adjacent bone enlargement, and management is challenging due to poor connective tissue self-regeneration. This study compared the effects of proximal fibular osteotomy (PFO) alone versus PFO with intra-articular hyaluronic acid injections (IAHA) among patients presenting with knee OA. Methods: A quasi-experimental study was done at Ziauddin Hospital's orthopedics department from March 2020 to March 2021. Patients with medial compartment knee joint OA requiring surgery aged≥40 years and BMI of <30kg/m2 were included. All participants were assigned into two groups, PFO was done alone in group A (n=30) and with IAHA in group B (n=30). Both groups had their medial joint spaces measured and documented pre- and post-operatively, as well as their Oxford knee score and visual analog scale (VAS). SPSS version 25 was used and the normality of data was assessed using Shapiro-Wilk's test. The mean difference (post-pre) was compared using the Mann-Whitney U test. A p≤0.05 was statistically significant. Results: A total of 60 patients were included with a mean age of 51.30±4.87 in Group A and 50.83±6.17 in Group B. Outcomes in both groups were improved considerably with a significant p<0.0001 in groups, in terms of pain and function determined using Oxford knee score, medial joint space measurement, and VAS score. Conclusion: PFO alone and PFO with IAHA show significantly improved results in terms of functional outcomes, but the use of IAHA in combination with PFO, has considerably better results in terms of pain relief.